If a = lo g 1 2 1 8 and b = lo g 2 4 5 4 , find the value of:
( a + b ) 2 + a ( 1 0 − a ) − b ( 1 0 + b )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can re-write the given expression as
( a + b ) 2 + a ( 1 0 − a ) − b ( 1 0 + b ) = 2 a b + 1 0 a − 1 0 b = 2 ( a − 5 ) ( b + 5 ) + 5 0
We now rewrite the two logs with a common base. Since both given bases and both given arguments are of the form 2 m 3 n , we choose base 2 (base 3 would work equally well.)
a = lo g 1 2 1 8 = lo g 2 1 2 lo g 2 1 8 = 2 + lo g 2 3 1 + 2 lo g 2 3 b = lo g 2 4 5 4 = lo g 2 2 4 lo g 2 5 4 = 3 + lo g 2 3 1 + 3 lo g 2 3 ⟹ ⟹ a − 5 = 2 + lo g 2 3 - 9 − 3 lo g 2 3 = 2 + lo g 2 3 - 3 ( 3 + lo g 2 3 ) b + 5 = 3 + lo g 2 3 1 6 + 8 lo g 2 3 = 3 + lo g 2 3 8 ( 2 + lo g 2 3 )
Then, returning to the expression above,
2 ( a − 5 ) ( b + 5 ) + 5 0 = 2 [ 2 + lo g 2 3 - 3 ( 3 + lo g 2 3 ) ] [ 3 + lo g 2 3 8 ( 2 + lo g 2 3 ) ] + 5 0 = 2 ( - 3 ) ( 8 ) + 5 0 = 2
Problem Loading...
Note Loading...
Set Loading...